RENCANA PENGEMBANGAN DAN PENGELOLAAN LANSKAP KAWASAN OBYEK WISATA DANAU KERINCI, KABUPATEN KERINCI, JAMBI - Febrian Miandy; Hadi Susilo Arifin (Jurnal Lanskap Indonesia, 2010)
Kerinci Lake tourism area is located in Kerinci Seblat National Park area, consists of swamp and lake areas that maintain its beauty and natural ecosystem. This research was conducted to study and to analyze the existing condition of Kerinci Lake tourism area and to arrange the development and managementplan of this area. This research used survey method. The result of this research wasa development and management recommendation, consisted of space concept and siteplan according to the nature preservation, conservation and convenience so that  the potency can be used spreadly according to the environmental and cultural value of Kerinci District.The recommended development and management plan is  spatial zoning, such as intensive recreation zone, semi-intensive recreation zone, passive recreation zone, conservation zone and circulation zone. The zoning  includes a space arrangement to confined the recreation activity based to the confined source of activity’s capacity and the visit intensity. It also puts some attentions to the planing and confined development rules in Kerinci District. The next zoning is the management zoning such as intensive management zone, semi-intensive management zone, and non intensive management zone. This zoning based on thelevel and amount of the visitors, the activity level, visit duration and the damage (vandal) level in a recreation site.